LEGALITY OF TERMINATION OF CONSTITUTIONAL JUDGES BY THE COUNCIL OF REPRESENTATIVES BEFORE THEIR TERMS OF OFFICE END: LEGALITAS PEMBERHENTIAN HAKIM KONSTITUSI OLEH DEWAN PERWAKILAN RAKYAT SEBELUM MASA JABATAN BERAKHIR - Aulia Oktarizka Vivi Puspita Sari A.P; Indah Satria (Constitutional Law Society, 2023)
Constitutional judges must have integrity and personality that is beyond reproach, be fair, be a statesman who masters the constitution and state administration, and not concurrently serve as a state official. Dismissal of constitutional judges before the end of their term of office can only be carried out for reasons, namely resigning at their own request submitted to the chairman of the Constitutional Court, being physically or mentally ill continuously for 3 (three) months so that they cannot carry out their duties as evidenced by a doctor's certificate , as well as dishonorably dismissed for reasons as set out in Article 23 paragraph (2) of the Constitutional Court Law. Related to the legality of dismissal of Constitutional Justices by the House of Representatives before the term of office ends. This type of research is normative legal research or normative juridical. A dishonorable dismissal of a Constitutional Judge can only be carried out if the reasons for dismissal are met in accordance with the provisions in Article 23 paragraph (2) of the Constitutional Court Law. Whereas the House of Representatives is only capable of nominating candidates for Constitutional Justices through an application to the President at the request of the Chief Justice of the Constitutional Court which will then be determined based on a Presidential Decree. After the Constitutional Court accepts the Presidential Decree, the Presidential Decree will be notified to the institution authorized to apply for a replacement of Constitutional Judges